Change content and aid effectiveness : how the size of change content affects implementation of technical assistance recommendations in developing Pacific Island countries - Cotton, Margaret (Massey University, 2008)
International aid agencies offer development aid with the expectation that developing countries will transform to such an extent that they can look after themselves, yet many countries have not developed as expected. This study identifies how the size of the change content of technical assistance recommendations affects their implementation: Technical assistance recommendations from the Pacific Financial Technical Assistance Centre, Fiji, to developing Pacific Island countries were studied. A content analysis was conducted to assess size using traditional transactional and transformational change definitions, and a survey questionnaire was used to assess size from the perspective of the technical assistance recipients. The content analysis findings suggest the majority of the changes are transactional, whereas, the recipients have rated the majority of the changes as large. The recipient’s perspective of size was most indicative of the likely implementation of the change. Changes rated as ‘small’ by the recipients are almost certain to be implemented whereas changes rated as ‘large’ have only a one-in-three chance of being implemented. If technical assistance recommendations are transactional manageable reforms in the eyes of aid agencies but are not seen the same way by recipients the chances a recommendation will be implemented, and the technical assistance successful, are compromised. The study supports the notion that to be effective technical assistance recommendations need to be seen through the eyes of the recipient.
Keywords: Development aid; Developing countries; Technical assistance; Change implementation; Pacific Island countries; Pacific Financial Technical Assistance Centre, Fiji; Aid effectiveness; Fields of Research::340000 Economics::340200 Applied Economics::340213 Economic development and growth